Nanobubble Ozone Stored in Hyaluronic Acid-Decorated Liposome Solutions: Inactivating Antibiotic-Resistant Bacteria and Genotoxicity, Sub-Acute and Sub-Chronic Toxicity Tests - Erkan Alkan P; Karabiyik T (Infection and Drug Resistance)
Perihan Erkan Alkan,1 Talha Karabiyik2 1Department of Medical Microbiology, Faculty of Medicine, Bandırma Onyedi Eylül University, Bandırma,/Balıkesir, Turkey; 2Department of Medical Biochemistry, Faculty of Medicine, Bandırma Onyedi Eylül University, Bandırma/Balıkesir, TurkeyCorrespondence: Perihan Erkan Alkan, Bandırma Onyedi Eylül University, Faculty of Medicine, Department of Medical Microbiology, Bandırma/Balıkesir, Türkiye, Tel +905331683073, Email palkan@bandirma.edu.trIntroduction: Nanobubble ozone stored in hyaluronic acid-decorated liposomes (patent application PCT/TR2022/050177) was used, and the Minimum Inhibitory Concentration (MIC) was found to be 1562 ppm. Pseudomonas aeruginosa (patient isolate), Acinetobacter baumannii (patient isolate), Methicillin-Resistant Staphylococcus aureus (MRSA) (ATCC12493), and Escherichia coli (ATCC25922) bacteria, which are hospital-acquired and healthcare-associated infections, were used. A time-dependent efficacy study was conducted at 1600 ppm. Our study aimed to determine whether the newly developed solution maintains long-term effectiveness and can be used as an antibacterial agent, especially in intensive care units.Methods: Antibacterial tests of the nanobubble liposome solution, developed with a different technique than the standard ozonation procedures, were performed with the CLSI M07 A9 (Methods for Dilution Antimicrobial Susceptibility Tests for Bacteria That Grow Aerobically; Approved Standard) standard test method, and the solution was tested at Minimal Inhibitory Concentration (MIC) value and time-dependent effects were determined. For the stability test of the nanobubble liposome solution, according to the ASTM F 1980 standard, it was kept at 55 °C for 74 days as two-year stability.Results: The MIC of the nanobubble ozone solution was 1.562 ppm for MRSA and E. coli (ATCC 25922) standard test method using CLSI M07 A9 (Methods for Dilution Antimicrobial Susceptibility Tests for Bacteria That Grow Aerobically; Approved Standard). P. aeruginosa, A. baumannii, Methicillin-Resistant Staphylococcus aureus (MRSA) (ATCC12493), and E. coli (ATCC 25922). No activity was observed at 2 min, but 1600 ppm nanobubble liposomes at 10 min were found to be effective. In terms of effectiveness, the solution would still be effective after 2 years according to the ASTM F 1980 standard, contrary to expectations.Conclusion: It is thought that nanobubble ozone stored in hyaluronic acid-decorated liposome solutions will play an important role in the fight against infections because of its non-toxic effect, effectiveness against resistant bacteria, and stability for at least two years. In the following process, it would be appropriate to support the product through clinical studies.Keywords: nanobubble liposomes, ozone, NOHAL, antibacterial agents, genotoxicity, sub-acute toxicity, sub-chronic toxicity